Asymmetric information in automobile insurance: Evidence from driving behavior - Daniela Kremslehner; Alexander Muermann (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
Based on a unique data set of driving behavior we find direct evidence that private information has significant effects on contract choice and risk in automobile insurance. The number of car rides and the relative distance driven on weekends are significant risk factors. While the number of car rides and average speeding are negatively related to the level of liability coverage, the number of car rides and the relative distance driven at night are positively related to the level of first-party coverage. These results indicate multiple and counteracting effects of private information based on risk preferences and driving behavior.
urn:nbn:de:hebis:30:3-416822
Keywords: 330